A comparison between numerical predictions and experimental results for horizontal core-annular flow with a turbulent annulus. (October 2017) - Ingen Housz, E.M.R.M.; Ooms, G.; Henkes, R.A.W.M.; Pourquie, M.J.B.M.; Kidess, A.; Radhakrishnan, R.
Highlights: Viscous oil experiments were done in horizontal core-annular flow with a turbulent water annulus. Numerical simulations were performed with a k –ε model at time-dependent, 3D conditions. The simulations give a 15% lower pressure drop than the experiments. Abstract: An experimental and numerical study has been performed for oil–water core-annular flow in a horizontal pipe, with a special focus on the effect of the presence of the turbulence in the water annulus. An experimental set-up was built and the obtained experimental results were used for the validation of numerical simulations that were carried out as well. The oil density was considerably lower than the water density, which leads to a rather eccentric oil core. The numerical simulations were carried out for different time dependent, fully 3D conditions. Only when a turbulence model is applied (instead of assuming laminar flow) the agreement between the predictions and the experiments is reasonably good.